Stigma Kekerasan dan Pudarnya Institusi Pernikahan: Analisis Kualitatif Pandangan Karyawan PT. SiCepat Ekspres Indonesia - Pangesti, Astri Indah; Sihombing, Grace Prima Apriani; Mira Oktaviana Whisnu Wardhani (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
Marriage has an important role in shaping the family structure in society. However, in recent years, the marriage rate in Indonesia has experienced a significant decline, reaching 7.51% in 2023. This decline is caused by various factors, one of which is the increase in cases of Domestic Violence (KDRT), which gives a negative image to the institution of marriage. This article aims to examine the stigma of violence and the fading of the institution of marriage. This research aims to analyze the views of employees of PT. Sicepat Express Indonesia from 2018 to 2023. This study uses a qualitative descriptive method to understand employees' views on this issue.  Based on data, in 2023 there will be 289,111 cases of violence against women and 351,828 divorces, of which domestic violence is the main factor. The results show that many individuals feel worried and reluctant to get married due to the growing negative stigma. These findings reveal that domestic violence not only has a direct impact on victims, but also affects the way people, especially the younger generation, view marriage as an institution that ideally brings happiness.